China in the new international economic order : new directions and changing paradigms - Toohey, Lisa; Picker, Colin, 1965-; Greenacre, Jonathan (New York : Cambridge University Press, 2015)
'The enormous economic power of the People's Republic of China makes it one of the most important actors in the international system. Since China's accession to the World Trade Organization in 2001, all fields of international economic law have been impacted by greater Chinese participation. Now, just over one decade later, the question remains as to whether China's unique characteristics make its engagement fundamentally different from that of other players. In this volume, well-known scholars from outside China consider the country's approach to international economic law. In addition to the usual foci of trade and investment, the authors also consider monetary law, finance, competition law, and intellectual property. What emerges is a rare portrait of China's strategy across the full spectrum of international economic activity.'--
China In The International Economic Order : New Directions And Changing Paradigms / Colin B. Picker and Lisa Toohey -- Revamping the China Model for the Post-Global Financial Crisis Era : The Emerging Post-Washington, Post-Beijing Consensus / Randall Peerenboom -- Regarding China : Images of China in the International Economic Order / Lisa Toohey -- China and International Tribunals : Onward from the WTO Marcia / Don Harpaz -- China's Legal Cultural Relationship to International Economic Law : Multiple and Conflicting Paradigms / Colin B. Picker -- From the Doha Round to the China Round : China's Growing Role in WTO Negotiations / Henry Gao -- China's Implementation of WTO Decisions / Timothy Webster -- The Emerging Rules on State Capitalism and their Implications for China's Use of SOEs / Junji Nakagawa -- Standards as a Means to Technological Leadership? : China's ICT Standards in the Context of the International Economic Order / Shin-yi Peng -- China's Negotiation of the International Economic Legal Order / Ross P Buckley and Weihuan Zhou -- Is the Rise of Chinese State Capital A Regulatory Game Changer? : The Example of Inward Investment Capital to Australia / Justin O'Brien, George Gilligan and Jonathan Greenacre -- Contesting the Liberal Imaginary? : China's Role in the International Monetary System / Julian Gruin -- China, Economic Taoism and Development : Different Paradigms, Different Outcomes / Xuezhu Bai and Nicholas Morris -- Chinese Companies and Outbound Investment : The Balance between Domestic and International Concerns / Vivienne Bath -- Mergers with Conditions in China : Caution, Control or Industrial Policy? / Deborah Healey -- Geo-Politics, China and Investor-State Arbitration / Leon E. Trakman -- China, Intellectual Property Rights and the WTO : Challenging but not a challenge to the existing legal order / Bryan Mercurio.
Includes bibliographical references and index.
Keywords: Foreign trade regulation -- China -- Congresses; Investments, Foreign -- Law and legislation -- China -- Congresses; International law -- China -- Congresses; China -- Foreign economic relations -- Congresses